2022
DOI: 10.7554/elife.78542
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide screen of prelimbic cortex inputs reveals a functional shift during early fear memory consolidation

Abstract: Memory formation and storage rely on multiple interconnected brain areas, the contribution of which varies during memory consolidation. The medial prefrontal cortex, in particular the prelimbic cortex (PL), was traditionally found to be involved in remote memory storage, but recent evidence points toward its implication in early consolidation as well. Nevertheless, the inputs to the PL governing these dynamics remain unknown. Here, we first performed a brain-wide, rabies-based retrograde tracing screen of PL e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…Adding to the known involvement of the RSC [55,56] and the Re [57][58][59] in modulating fear memory formation and expression, our results revealed neural activity in these structures was increased during mild memory recall, but not during strong memory recall, when compared to unshocked controls. Although the hippocampus [48,49,[60][61][62], prelimbic [63][64][65], and cingulate cortex [66][67][68] are critical to contextual fear memory-related processes, we found no differences in their activation between groups, suggesting that the role of these structures in modulating the expression of fear of different intensities may not reflect in changes in overall activation levels.…”
Section: Discussioncontrasting
confidence: 71%
“…Adding to the known involvement of the RSC [55,56] and the Re [57][58][59] in modulating fear memory formation and expression, our results revealed neural activity in these structures was increased during mild memory recall, but not during strong memory recall, when compared to unshocked controls. Although the hippocampus [48,49,[60][61][62], prelimbic [63][64][65], and cingulate cortex [66][67][68] are critical to contextual fear memory-related processes, we found no differences in their activation between groups, suggesting that the role of these structures in modulating the expression of fear of different intensities may not reflect in changes in overall activation levels.…”
Section: Discussioncontrasting
confidence: 71%
“…The claustrum provides a diffuse excitatory connection to almost all cortical regions [1][2][3][4][5] . The function of the claustrum has remained somewhat enigmatic as it has been implicated in cortical synchrony, sleep, stress, memory, attention, and decision making [6][7][8][9][10][11] . One challenge has been relating neural activity in the claustrum to these distinct processes, as the real-time measurement of identified claustrum neurons has only been reported in a select few instances 6,7,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…in synchronized cortical states. However, the claustrum is also proposed to function in REM sleep and states of high attentional demand such as memory encoding or decision making 8,10,11,37,38 , suggesting activation during cortical desynchronization. This work raises the question of whether there is an optimal brain or behavioral state for claustrum communication with downstream targets in the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, blockade of mGlu5 in thalamus also inhibited pain behaviors ( Fig. 2 ), possibly through projections to cortical regions such as somatosensory and insular cortices, with the latter projecting strongly to the prelimbic cortex ( 46 ). Previous studies showed increased mGlu5 receptor expression in the mPFC ipsilateral, but not contralateral, to peripheral nerve injury ( 45 ).…”
Section: Discussionmentioning
confidence: 97%